Struktur Dan Desain Organisasi - Nurulli Fatur Rohmah (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2019)
Organization is a very important element in modern society both in the public sector (State) and in the private sector. Each organization has certain boundaries (boundaries), so that someone who has an interaction with other parties does not of their own volition, they are limited by certain rules. Therefore each organization has a different structure that can influence the attitudes and behavior of its members.Organizational structure is a formal pattern that aims to group people and jobs, formal patterns of activity and relationships between various subunits of the organization, which are often described through charts. Things to note: 1). Basics of Organizational Structure: Work specialization, Depertementalization, Command Chain, Control Chain, Centralization and Decentralization, and Formalization. 2). Organizational Principles: Clear formulation, appreciation, division of labor, delegation of authority, application of hierarchy, unity of direction, unity of command, limit of supervisory ability. 4). Organizational foundations: formulation of objectives, division of tasks, coordination, delegation of authority, range of control, level of organization, flexibility. 5). Forms in organizational structure: line form, line and staff form, functional form, and organizational form committee. 6). Work design: specialization / simplification and expansion of work. Modern organizational design: horizontal design and network design